From HIV diagnosis to initiation of treatment: Social transformation among people starting antiretroviral therapy in Peru. (January 2017) - Waters, Chloe; Wong, Milagros; Nelson, Adrianne Katrina; SantaCruz, Janeth; Beeson, Amy; Pfeiffer, James; Muñoz, Maribel; Castro, Arachu; Shin, Sonya
Social support is a key, yet elusive resource for HIV patients living in poverty in Lima, Peru. Despite a greater need for health services and encouragement from others, economic restraints, stigma, and trouble negotiating a fractured health system act as hurdles to accessing support. In this study, 33 people with HIV and 15 of their treatment supporters were interviewed upon initiation of antiretroviral therapy in order to understand changes in social support during this critical time, and how these changes affected their well-being. Everyone's social network underwent dramatic transformation, while some were rejected upon disclosure by people they knew, many successfully trimmed their social circles to a few trusted parties. Treatment supporters were most frequently the first to whom they disclosed their HIV status, and most backed the person with HIV, although sometimes out of obligation. HIV peers became a vital new source of strength. Ultimately, people with HIV who successfully reorganized their social network drew personal strength and self-worth from new and old relationships in their lives.